Answer:
(4,11)
Explanation:
Given two coordinates (x₁, y₁) and (x₂,y₂), the midpoint of the coordinates is expressed as M(X,Y) =
where;
![X = (x_1+x_2)/(2)\ and \ Y = (y_1+y_2)/(2)](https://img.qammunity.org/2021/formulas/mathematics/college/n1zzg789z9ul7of2qitm1lmaj6ojxujlm5.png)
Given the midpoint (X, Y) = (1,6) and one end point to be (-2,1), to get the unknown endpoint (x,y), we will apply the formula above. from the coordinates given X = 1, Y = 6, x₁ = -2 and y₁ = 1
![Given \ X = (x_1+x_2)/(2)\\1 = (-2+x)/(2)\\cross \ multiply\\2 = -2+x\\x = 2+2\\x = 4](https://img.qammunity.org/2021/formulas/mathematics/college/r568lpwkr84u95nowdkxu0mxyc4y2msfra.png)
Similarly to get y;
![Given \ Y = (y_1+y)/(2)\\6 = (1+y)/(2)\\cross \ multiply\\2*6 = 1+y\\12 = 1+y\\y = 12-1\\y = 11](https://img.qammunity.org/2021/formulas/mathematics/college/zwqpvzzty6onrw1x8bkvhmsp6rpeqfrrt3.png)
Hence the unknown endpoint (x,y) is (4,11)